2019
DOI: 10.3928/01477447-20190424-08
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Lysis of Adhesions With Manipulation Under Anesthesia Versus Manipulation Alone in the Treatment of Arthrofibrosis After TKA: A Matched Cohort Study

Abstract: Arthrofibrosis following total knee arthroplasty (TKA) is a debilitating complication. Treatment options include physical therapy, manipulation under anesthesia (MUA), and arthroscopic lysis of adhesions (ALOA) with or without MUA. The authors studied 70 patients with arthrofibrosis after TKA treated with MUA or ALOA plus MUA. In this matched cohort study, 35 patients were treated with MUA and 35 patients were treated with ALOA plus MUA. Total knee arthroplasty followed by MUA was performed by 2 surgeons and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…[23] Additional studies have also supported the role of arthroscopic LOAs in the stiff TKA [11,22,24,25]. Volchenko et al [26] performed a matched-cohort study of 70 total patients with post-TKA arthrofibrosis. One cohort was treated with a closed MUA alone and another with an arthroscopic LOA combined with MUA.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…[23] Additional studies have also supported the role of arthroscopic LOAs in the stiff TKA [11,22,24,25]. Volchenko et al [26] performed a matched-cohort study of 70 total patients with post-TKA arthrofibrosis. One cohort was treated with a closed MUA alone and another with an arthroscopic LOA combined with MUA.…”
Section: Discussionmentioning
confidence: 97%
“…On average, patients in our study underwent arthroscopic LOA 57.2 months after their index TKA. The majority of prior studies which have investigated arthroscopic LOA with or without closed MUA for arthrofibrosis have included patients within 1 year from index TKA [11,[23][24][25][26]. Volchenko et al did report a diminished benefit of arthroscopic LOA þ MUA when performed later from index TKA; however, this was stratified at the 12-week postoperative mark [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arthroscopic lysis with MUA yielded changes in ROM: a 72.7% increase 4 to 12 weeks after index TKA (p = 0.032), a 50.0% increase 12+ weeks after TKA (p = 0.032), and a 99.8% increase in patients with a pre-manipulation ROM of 0-60 degrees (p = 0.001). MUA alone yielded a 49.2% increase 4 to 12 weeks after index TKA (p = 0.161), a 27.0% increase 12+ weeks after TKA (p = 0.161) and a 68.8% increase in patients with pre-manipulation ROM of 0 to 60 degrees [41]. Authors concluded arthroscopic lysis of adhesions plus MUA led to greater increases in ROM (p = 0.026) and final knee flexion (p = 0.028) compare with those treated with MUA alone.…”
Section: Surgical Treatmentmentioning
confidence: 96%